Montrul, Silvina: The acquisition of heritage languages - Putnam, Michael T. (Norsk Lingvistisk Tidsskrift, 2017)
The last two decades have witnessed a dramatic increase in the interest in heritage language acquisition, maintenance, and attrition by both scholar and layman alike. The formal study of heritage languages and the status of their grammars have in many ways served as an important missing, complementary subfield of inquiry in our quest to better understand bi- and multilingual grammars in the mind and society. To date, what this nascent field has been sorely lacking is a volume - or a canonical set of works - that functions as a solid reference upon which future research can be built. In this work Silvina Montrul takes on the unenviable task of presenting this type of reference work for both specialist and neophyte to this ever-growing field of study. In my estimation, this book is an invaluable resource for a wide audience, although it is probably most useful for scholars new to the field.